Developing TPR Vocabulary Peer Assessment in Primary School Classroom Practices - Suciana Wijirahayu; Ria Septiani (UICELL, 2017)
This study was conducted to improve students’ vocabulary mastery of the 2nd grader in a private primary school in Tangerang Indonesia. A classroom action research was initiated for the development. It was found in the preliminary observation that there were problems and weakness in students’ vocabulary mastery therefore suitable strategies to overcome that problem need to be employed. There are many aims of peer assessment, yet in this case it essentially involves young EFL learners as participants in providing feedback to others on the quality of their work. The students enjoyed to have the opportunity to assess their partner’s performance in doing TPR activities. There was a lot of fun when pair of student doing this Peer Assessment. One of them did the action based on the command in the rubric sheet while their partner guessed the correct command in accordance to what have their partner’s movements. Based on the students’ result of peer assessment activity in learning English vocabulary, it was found that students were so motivated and tried hard to do the best their performance. They realized that their partners will assess them, so they were enthusiastic to do TPR correctly. The vocabulary mastery improvement could be observed from the results of the students’ peer assessment score in each cycle.